Estudo de associação genética no angioedema induzido por anti-inflamatórios não-esteroidais - Ensina, Luis Felipe Chiaverini [UNIFESP] (2017)
Introduction: Non-steroidal anti-inflammatory drugs (NSAID) are the main cause of drugs hypersensitivity reactions in our circle. Non-selective hypersensitive is the most common type, occurring with any NSAID, independently of its chemical structure, and presenting with anaphylaxis, urticaria or angioedema. The mechanism involved is supposedly related to the cyclooxygenase inhibition, and genetic polymorphisms that regulate or increase the expression of leukotrienes related genes could be risk factors for NSAID hypersensitivity. Objectives: To detect possible genetic markers by exome sequencing, that determine a hypersensitivity response in patients with NSAID induced isolated angioedema. Methods: We selected four trios (patients with an isolated angioedema induced by multiple NSAID and its respective parents) for exome sequencing, a technic that allows checking the biologic active part of the genome (exons). Results: It was not possible to determine any significant biological variable in the genes related to arachidonic acid metabolism, or in any of the other genes previously related to NSAID hypersensitivity. We observed a polymorphism in gene MUC5B in three of the four families, possibly indicating the existence of other mechanisms related to the reaction. Conclusions: We did not find any mutation directly related to NSAID induced angioedema in the studied group. A validation and deeply study of the biological effects of the MUC5B variable in the families studies should be performed.